Cuproptosis regulator-mediated patterns associated with immune inﬁltration features and construction of cuproptosis-related signatures to guide immunotherapy - Wang, Gongjun; Xiao, Ruoxi; Zhao, Shufen; Sun, Libin; Guo, Jing; Li, Wenqian; Zhang, Yuqi; Bian, Xiaoqian; Qiu, Wensheng; Wang, Shasha (Frontiers in Immunology, 2022)
Background: Liver hepatocellular carcinoma (HCC) is a prevalent cancer that lacks a sufficiently efficient approach to guide immunotherapy. Additionally, cuproptosis is a recently identified regulated cell death program that is triggered by copper ionophores. However, its possible significance in tumor immune cell infiltration is still unclear. Methods: Cuproptosis subtypes in HCC were identified using unsupervised consensus cluster analysis based on 10 cuproptosis regulators expressions, and a cuproptosis-related risk signature was generated using univariate and LASSO Cox regression and validated using the ICGC data. Moreover, the relationship between signature and tumor immune microenvironment (TME) was studied through tumor immunotherapy responsiveness, immune cell infiltration, and tumor stem cell analysis. Finally, clinical specimens were analyzed using immunohistochemistry to verify the expression of the three genes in the signature. Results: Two subtypes of cuproptosis regulation were observed in HCC, with different immune cell infiltration features. Genes expressed differentially between the two cuproptosis clusters in the TCGA were determined and used to construct a risk signature that was validated using the ICGC cohort. Greater immune and stromal cell infiltration were observed in the high-risk group and were associated with unfavorable prognosis. Elevated risk scores were linked with higher RNA stemness scores (RNAss) and tumor mutational burden (TMB), together with a greater likelihood of benefitting from immunotherapy. Conclusion: It was found that cuproptosis regulatory patterns may play important roles in the heterogeneity of immune cell infiltration. The risk signature associated with cuproptosis can assess each patient's risk score, leading to more individualized and effective immunotherapy.